National and cultural specificity as the standard language and language variation main part - J Baghana; E V Bondarenko; О О Chernova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2012)
The article touches upon culture and language inner relation. These semiotic systems are characterized by mutual influence. Language is a part of a nation cultural inheritance. That is why culture affects it. There is a backward process, where a language influences culture.